IT in the “alojamento local” type of accomodation: The case of the Alentejo region: The reality of AL in the Alentejo region - Bello Moraes, Pedro (Aprender, 2023)
The Alojamento Local (AL) classification was created in Portugal in March 2008. Online booking platforms, such as airbnb, are identified as one of the key factors that led to the exponential growth of this type of offer.The main objective of this paper is to evaluate the relevance of the information and communication technologies (ICT’s) for the Alentejo region AL businesses owners, as well as the training needs, they identify in this area.To achieve this goal, an online form was developed and sent to all owners of AL establishments in the Alentejo region followed by a quantitative analysis of the results.The investigation allow us to conclude that the use of ICT is particularly important in these accommodation businesses and that specific training in this sector is seen by most agents as remarkably relevant.
Keywords: Alojamento Local; Accomodation management; Alentejo Tourism; ICT in Tourism